PRAKTIK KECURANGAN AKUNTANSI DALAM PERUSAHAAN - Putra, Yuniarti Hidayah Suyoso (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
This paper describes accounting fraud in company. Previous researches indicate several factors driven accounting fraud such as opportunity, exposure, individual aspect, poor internal control, and ineffective employeeâ€™s placement and management model. Recurrence of accounting fraud is happened either because of well planned and perpetrators are forced to do it. However, diverse methods can be conducted to detect and prevent accounting fraud and is supported by high moral commitment and law enforcement. Â Key Words: Kecurangan akuntansi, pendeteksian dan pencegahan.